Preparedness for practice : new social workers and the core competence standards : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work, Massey University, Manawatū, Aotearoa New Zealand - Taylor Moore, Scott (Massey University, 2023)
This thesis examines how newly qualified social workers (NQSW) perceive their readiness to practise social work measured against the Social Workers Registration Board (SWRB) core competence standards. The research also explores what additional skills, knowledge and training they think they need to assist them in their social work role. The findings were evaluated using the literature from both Aotearoa New Zealand and internationally. In general, the literature indicated that NQSW do think that their education has prepared them for practise, with some studies expressing concerns about the working environments that they are graduating into. Graduates need to be supported once in employment and their profession requires a lifelong, learning, journey, and they should not be expected to begin practice with advanced skills. A qualitative methodology informed by a social constructionist framework and critical theory was used to explore the research questions. The data was collected using semi structured interviews with nine NQSW. Thematic analysis was employed to process the rich data and identify themes that assisted in addressing the research questions. There are limitations to the study: it is a small sample size, and the participants self-selection may influence the findings. There were demographic limitations too as the research did not gather specific data regarding, age and disability, or if they were from urban or rural environments. Another limitation related to the impact of COVID-19 restrictions at the time of the interviews which required the use of online interviews for some participants. The research findings support previous studies, where participants generally expressed a positive view regarding how their study had prepared them to practise social work. Field education placements remain a significant strategy for contributing to the sense of preparedness of NQSW. The findings highlight the wide range of perceptions regarding competence after graduating and a NQSWs journey from education to employment. It captured the sense of preparedness of NQSWs and how this is affected by the skills, knowledge and training gaps in their practice and also by the teaching and the learning of the competence standards. Preparedness was also found to be impacted by the COVID-19 pandemic. The use of graduate support programmes to assist in transitioning from academia to employment was also noted. A recommendation from this study is that there is benefit in more longitudinal studies to be completed into the field of readiness to practise in Aotearoa New Zealand. Due to the modest size of the study, it would be beneficial for a larger study to be undertaken using a larger sample size. Future research could capture additional demographic data that includes participants’ disabilities, caring responsibilities and if they are practising in a rural environment. Consideration of how NQSW might develop greater awareness of macro level social work was also a recommendation from the research. Due to the varied awareness of the competence standards by participants and the different curriculum in higher education institutions, a capabilities framework, rather than core competence standards, might be a more reliable measure to assess the perception of readiness of NQSW.
Keywords: 440901 Clinical social work practice